Supervisors’ Digital Competence and Its Influence on the Quality of Islamic Education Teachers in Madrasah Ibtidaiyah - Amir Mahmud,; Supriyoko,; Mufrod Teguh Mulyo,; Muhammad Hamid Alwi, (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2025)
Objectives: This research aims to analyze the influence of supervisors’ digital competence on the quality of Islamic education teachers in Madrasah Ibtidaiyah. Method: This study employed a quantitative approach with a causal-correlational design. The population consisted of Islamic Religious Education (IRE) supervisors at Madrasah Ibtidaiyah in Central Java, with a sample of 100 individuals. The sample was selected using proportional cluster random sampling. Data were collected using a questionnaire tested for validity and reliability. The data were analyzed using the Kolmogorov-Smirnov test, scatter plot technique, t-test, F-test, and regression analysis. Results: The results showed that supervisors’ digital competence had a significant influence on the quality of Islamic education teachers in Madrasah Ibtidaiyah, with a contribution of 36.2%. Theoretical Contribution: This study enriches Islamic education theory by demonstrating that supervision aligns with the principles of al-mas'ūliyyah (professional responsibility), al-amānah (trust and integrity), al-iḥsān (continuous improvement), ash-shūrā (deliberation and collaboration), and at-taqwīm (evaluation and reflection), as well as mastery of technology as a manifestation of the command to iqra’ (exploration and development of knowledge). Implication: Future research should include additional variables such as school culture, technological support, and teacher motivation to develop a more comprehensive supervision model.